The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s0103-84782006000400051
|View full text |Cite
|
Sign up to set email alerts
|

Perspectivas para o desenvolvimento dos cultivos de camarões marinhos no estuário da Lagoa dos Patos, RS

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 4 publications
1
8
1
6
Order By: Relevance
“…The composition of the effluent water found in the present study, with high TAN concentrations and high N: P ratio, is typical of shrimp aquaculture waste, where ammonium is the main excess nutrient, due to the high protein ratios in the feed pellets (MacIntosh and Philips 1992; Jones et al 2001b). The maximum TAN and phosphate concentrations found in the present study are still low if compared with values found in ponds of intensive shrimp farms in Brazil (Marinho-Soriano et al 2002) and other tropical countries (Kinne et al 2001), probably due to the lower stocking densities in the ponds (25 animals m −2 ) and the high efficiency of the feeding mechanism used (Poersch 2004). The concentrations found here, however, are still very high compared to recorded values in local estuarine waters (Baumgarten et al 1995).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The composition of the effluent water found in the present study, with high TAN concentrations and high N: P ratio, is typical of shrimp aquaculture waste, where ammonium is the main excess nutrient, due to the high protein ratios in the feed pellets (MacIntosh and Philips 1992; Jones et al 2001b). The maximum TAN and phosphate concentrations found in the present study are still low if compared with values found in ponds of intensive shrimp farms in Brazil (Marinho-Soriano et al 2002) and other tropical countries (Kinne et al 2001), probably due to the lower stocking densities in the ponds (25 animals m −2 ) and the high efficiency of the feeding mechanism used (Poersch 2004). The concentrations found here, however, are still very high compared to recorded values in local estuarine waters (Baumgarten et al 1995).…”
Section: Discussioncontrasting
confidence: 72%
“…Farming of the exotic Pacific white shrimp (Litopenaeus vannamei Boonei) has become established around Patos Lagoon estuary and is expected to cover more than 100 ha by 2009 (Poersch et al 2006). Although state legislation and local shrimp culture conditions (e.g., semiintensive cultivation, use of sedimentation basins, preservation of wetlands and dunes) (Poersch et al 2006) are ecologically more acceptable than those applied in northeastern Brazil (Marinho-Soriano et al 2002;Lacerda et al 2006) and other tropical regions (Primavera 1994;Paéz-Osuna 2001), the use of biofiltering organisms to reduce inorganic nutrient loads still needs to be developed.…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, as condições climáticas favoráveis e o domínio das tecnologias de produção transformaram o país em principal produtor de camarões das Amé-ricas (Poersch et al, 2006). Parte do camarão produzido é comercializada congelada, sem o cefalotórax, ou na forma de filé, gerando grande quantidade de resíduos, que muitas vezes são descartados incorretamente, podendo acarretar problemas ambientais.…”
Section: Introductionunclassified
“…Devido às condições climáticas locais, o período de cultivo do camarão marinho fica restrito aos meses de verão (Freitas, 2006;Poersch et al, 2006), onde além de temperaturas mais elevadas, a baixa pluviosidade favorece maior salinização da água estuarina local devido ao aporte da água marinha (Poersch et al, 2006;Rosa & Bemvenuti, 2006). Durante o resto do ano, os viveiros permanecem secos, exceto pelo acúmulo ocasional de água da chuva, o que poderia favorecer a ocorrência de organismos límnicos como Chironomidae, os quais foram observados apenas no inicio do cultivo (Tab.…”
Section: Discussionunclassified